If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + -9) + -5 = 5(x + -4) + 50 Reorder the terms: 5(-9 + 3x) + -5 = 5(x + -4) + 50 (-9 * 5 + 3x * 5) + -5 = 5(x + -4) + 50 (-45 + 15x) + -5 = 5(x + -4) + 50 Reorder the terms: -45 + -5 + 15x = 5(x + -4) + 50 Combine like terms: -45 + -5 = -50 -50 + 15x = 5(x + -4) + 50 Reorder the terms: -50 + 15x = 5(-4 + x) + 50 -50 + 15x = (-4 * 5 + x * 5) + 50 -50 + 15x = (-20 + 5x) + 50 Reorder the terms: -50 + 15x = -20 + 50 + 5x Combine like terms: -20 + 50 = 30 -50 + 15x = 30 + 5x Solving -50 + 15x = 30 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -50 + 15x + -5x = 30 + 5x + -5x Combine like terms: 15x + -5x = 10x -50 + 10x = 30 + 5x + -5x Combine like terms: 5x + -5x = 0 -50 + 10x = 30 + 0 -50 + 10x = 30 Add '50' to each side of the equation. -50 + 50 + 10x = 30 + 50 Combine like terms: -50 + 50 = 0 0 + 10x = 30 + 50 10x = 30 + 50 Combine like terms: 30 + 50 = 80 10x = 80 Divide each side by '10'. x = 8 Simplifying x = 8
| 6x^2+42x-108=0 | | 7r^2+19r=36 | | 2+1=x | | 6(t-2)=18 | | 5(m+4)=20 | | -12=4(y-1) | | 6x^2=20x-16 | | -10=8m^2+21m | | -x^2+27x+28=0 | | 2(3x-8)-5=2(x-4)+23 | | 1.5x-.7=1.1-1.2x | | -8x-20=-x^2 | | 3(x-4)+3x=7-2(x-1) | | 27w+54=-3w^2 | | 2x^2-5x-60=-3x | | -6=3(y-2) | | x^2+13x+39=9 | | 4w-10+2w=74 | | -3x(2x+6)=0 | | 2x-7(3x+1)=(5-3x) | | 24x^2y-8xy+6xy^2=0 | | v^2-25=0 | | 5(6z-1)-2(z+7)=2(z+1) | | x^2-12x+52=0 | | v-25=0 | | 8+7(x-3)=6-6(x-6) | | 4x+5=-(x-30) | | 6a^2-486=0 | | -7x+13=-8 | | -5(3n+6)=5 | | 7x-3=3x+45 | | p=66-2q |